Effects of Teaching and Learning Supervision on Teachers Attitudes to Supervision at Secondary School in Kubang Pasu District, Kedah - Khun-inkeeree, Hareesol; Dali, Puteri Darishah; Daud, Yaakob; Omar Fauzee, Mohd Sofian; Khalid, Rozalina (2019)
This study was conducted to identify the influence of teaching and learning supervision on the attitude of teachers towards the supervision in secondary schools in Kubang Pasu District, Kedah. The supervisory model developed by Glickman, Gordon and Ross-Gordon (2004) and the research instrument involves a set of questionnaires containing 23 items. Respondents of the study involved 372 teachers in secondary schools in Kubang Pasu District, Kedah. The data were analyzed using descriptive statistics using Statistical Packages of Social Sciences and inferential statistics using the Partial Least Squares software through the SMART PLS 3.0 software. The result shows that there is a significant influence between the dimensions of knowledge and the technical skills with the teachers’ attitude towards supervision while the dimensions of interpersonal skills do not have a significant influence on teachers' attitudes. The findings can be used as guidance to the Ministry of Education, to overcome all the shortcomings and weaknesses in the existing teaching supervision practices based on the established supervisory regulation